Corrosion Resistance of Reinforcing Steel in Concrete Using Natural Fibers Treated with Used Engine Oil - Alejandro Flores Nicolás; Elsa C. Menchaca Campos; Mario Flores Nicolás; Omar A. Gonzalez Noriega; Cesar A. García Peréz; Jorge Uruchurtu Chavarín (Civil Engineering Journal, 2024)
The addition of natural fibers in the elaboration of concrete pastes has increased as an innovative alternative for the development of more ecological and environmentally friendly constructions. The objective of this research is to incorporate natural fiber residues from palm leaves and mango stone impregnated with used engine oil (UEO) in the cement matrix to improve the mechanical and electrochemical properties of reinforced concrete. Samples with fiber percentages of 0.2% and 0.4% with respect to the weight of the sand with a length of 10 mm were fabricated. Their properties, such as workability, air content, porosity, and compressive and flexural strength, were analyzed. To understand the corrosion rate of the steel bars, electrochemical techniques of corrosion potential, electrochemical noise, linear polarization resistance, and electrochemical impedance spectroscopy were applied to cubic samples exposed in a 3% sodium chloride saline environment for 365 days. The experimental results showed a positive effect on the corrosion phenomenon with the UEO and mango fiber treatment, decreasing the corrosion rate due to the formation of a protective film at the steel/concrete interface. Doi: 10.28991/CEJ-2024-010-04-02 Full Text: PDF